2019
DOI: 10.1016/j.bpj.2019.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Bilayers by Hemifusion: Method and Leaflet Behaviors

Abstract: We describe a new method to prepare asymmetric giant unilamellar vesicles (aGUVs) via hemifusion. Hemifusion of giant unilamellar vesicles and a supported lipid bilayer, triggered by calcium, promotes the lipid exchange of the fused outer leaflets mediated by lipid diffusion. We used different fluorescent dyes to monitor the inner and the outer leaflets of the unsupported aGUVs. We confirmed that almost all newly exchanged lipids in the aGUVs are found in the outer leaflet of these asymmetric vesicles. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 46 publications
4
81
0
Order By: Relevance
“…The atomistic simulations predict that inner leaflet lipids would have different physical properties from outer leaflet, consistent with extensive experimental observations of symmetric membranes. However, the biophysical consequences of lipid asymmetry in either model or biological membranes remain poorly understood because methodologies for constructing asymmetric model membranes have only recently become widely accessible 7 9 , 11 , 12 . We probed the biophysical asymmetry of live cell PMs using a fluorescent reporter of membrane packing (Di-4-ANEPPDHQ, Di4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The atomistic simulations predict that inner leaflet lipids would have different physical properties from outer leaflet, consistent with extensive experimental observations of symmetric membranes. However, the biophysical consequences of lipid asymmetry in either model or biological membranes remain poorly understood because methodologies for constructing asymmetric model membranes have only recently become widely accessible 7 9 , 11 , 12 . We probed the biophysical asymmetry of live cell PMs using a fluorescent reporter of membrane packing (Di-4-ANEPPDHQ, Di4).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, membrane asymmetries could be used as organellar identifiers for selective sorting of lipids and proteins between organelles. Finally, it has been shown that membrane asymmetry can affect the properties of membrane domains 9 , 11 , 43 and possibly the partitioning of proteins between ordered and disordered lipid environments 49 , 50 , making the magnitude and mechanisms of physical coupling between disparate leaflets in asymmetric membranes an essential open question 42 . Ultimately, deciphering the purpose of membrane asymmetry is central to understanding the functions of cell membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetrical membrane models have been developed in the last fifteen years, notably driven by the London [55,56] and Heerklotz [57,58] groups. They can be prepared by several methods, such as by using cyclodextrins as lipid carrier molecules [59], using enzymes [57], by different microfluidic technologies [60], or by hemifusion between models with different lipid compositions [61]. The development of these asymmetrical models has been mainly focused on mammalian lipid membranes.…”
Section: Biomimetic Membrane Modelsmentioning
confidence: 99%
“…Enoki and Feigenson demonstrated the power of their model to study coupling between the inner and outer leaflets (15). They could visualize the coupling of Lo and Ld domains in their asymmetric GUVs with a DSPC-DOPC-cholesterol inner leaflet and a DOPC-cholesterol outer leaflet.…”
mentioning
confidence: 99%